2015
DOI: 10.1515/ohs-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of epiphytic microcrustaceans in relation to different macrophyte microhabitats in a shallow wetland (Upo wetlands, South Korea)

Abstract: I n t e r n a t i o n a l J o u r n a l o f O c e a n o g r a p h y a n d H y d r o b i o l o g y AbstractMacrophytes determine the physical complexity of aquatic environments and provide a suitable habitat for colonization by microcrustaceans. We evaluated the effects of a seasonal growth pattern and structure of macrophyte species on epiphytic microcrustaceans collected from macrophyte surfaces (stems and leaves) in shallow wetlands from May 2011 to October 2012. In 2011, epiphytic microcrustaceans that pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Previous studies also observed cladoceran species such as C. sphaericus and M. microcopa in wetlands and shallow reservoirs where aquatic macrophytes were abundant [36,61]. These cladoceran species are more epiphytic than pelagic swimmers such as Daphnia or Bosmina; thus, substrate surfaces, such as the leaves and stems of macrophytes, are important for their distribution [62]. Choi et al [63] suggested that the different leaf and stem structures of aquatic macrophytes (e.g., emergent, floating, and submerged macrophytes) could affect the temporal and spatial distribution of epiphytic zooplankton species.…”
Section: Change Of Zooplankton Community Composition After Weir Openingmentioning
confidence: 83%
“…Previous studies also observed cladoceran species such as C. sphaericus and M. microcopa in wetlands and shallow reservoirs where aquatic macrophytes were abundant [36,61]. These cladoceran species are more epiphytic than pelagic swimmers such as Daphnia or Bosmina; thus, substrate surfaces, such as the leaves and stems of macrophytes, are important for their distribution [62]. Choi et al [63] suggested that the different leaf and stem structures of aquatic macrophytes (e.g., emergent, floating, and submerged macrophytes) could affect the temporal and spatial distribution of epiphytic zooplankton species.…”
Section: Change Of Zooplankton Community Composition After Weir Openingmentioning
confidence: 83%
“…Choi et al [ 43 ] suggested that the leaf or stem surface of aquatic macrophytes provides an appropriate substrate for epiphytic microinvertebrates. Moreover, epiphytic plankton attached to aquatic macrophytes are appropriate food sources for rotifers [ 44 ]. Areas well covered by aquatic macrophytes are also used as shelters for protection against physical disturbances, such as rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…From this point, we speculate that D. obtusa might have reduced bacterial abundance while swimming over the entire range in each beaker. Choi et al [38] suggested that C. sphaericus and S. vetulus mainly consume…”
Section: Discussionmentioning
confidence: 99%
“…From this point, we speculate that D. obtusa might have reduced bacterial abundance while swimming over the entire range in each beaker. Choi et al [ 38 ] suggested that C. sphaericus and S. vetulus mainly consume algae attached to the leaves and roots of aquatic macrophytes, such as Ceratophyllum demersum and Salvinia natans in wetlands, whereas their contribution to pelagic food sources is relatively low due to their limited movement. Thus, C. sphaericus and S. vetulus consume only bacteria around their locations, which might have a relatively modest effect of reducing ARB and tet (A) abundance.…”
Section: Discussionmentioning
confidence: 99%